Financialization of the economy and the need for personal finance advisory services - Krzysztof Waliszewski (e-Finanse: Financial Internet Quarterly, 2016)
Financialization of households is a result of the growing role of financial systems and instruments in the economy. The increased role of financial phenomena in financial and non-financial decisions taken by households is not proportional to capabilities of their perception and understanding by households which possess basic knowledge in finance. The missing link between institutions and financial markets offering more complex financial solutions and the consumer may be a financial advisor who can perform many important roles with respect to households. The aim of this article is to present financialization of the economy and households and the role that can be played by financial advisors in decreasing the imbalance of information between the consumer and financial institutions, as well as the lack of symmetry in understanding financial information by the consumer.
Keywords: D14; G23; 330; households financialization; personal financial advisor